Factors Associated with Fatigue in Patients Undergoing Radiotherapy: A Literature Review - Putra, Gian Dwi; Nelwati, Nelwati; Rahman, Dally (Indonesian Journal of Global Health Research, 2024)
Fatigue is one of the most common and disturbing symptoms among cancer patients, affecting almost all individuals undergoing radiotherapy, which lasts for a long time and interferes with the quality of life in performing daily activities. There has been a lot of research on the causative factors of fatigue in cancer patients undergoing radiotherapy. However, there is still a lack of literature review that looks at what are the factors that cause fatigue in cancer patients in general who undergo radiotherapy. This study aims to review existing literature to screen for factors contributing to fatigue in breast cancer patients undergoing radiotherapy. This study is a systematic review using The Joanna Briggs Institute Guideline and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Of the 220 articles found in PubMed, ScienceDirect, and JSTOR databases (years 2017-2022), 77 articles met the full-text access criteria. After rigorous selection, 7 articles were selected for analysis. These articles were reviewed using a quantitative analysis approach to identify demographic, clinical, treatment, and psychosocial factors associated with fatigue in cancer patients undergoing radiotherapy. The results showed that there are several factors that cause fatigue in cancer patients undergoing radiotherapy including demographic factors (age, occupation, education level), clinical factors (hemoglobin level, comorbidities, cancer stage), treatment factors (number of fractions, fraction dose), and psychosocial factors (insomnia, anxiety, and depression). Management of fatigue in cancer patients undergoing radiotherapy requires a comprehensive approach that considers demographic, clinical, treatment, and psychosocial factors that influence the patient's condition. Thus, effective interventions should include all these factors to improve patients' quality of life.